Facilitators and inhibitors in hospital-to-home transitional care for elderly patients with chronic diseases: A meta-synthesis of qualitative studies - Sun, Mengjie; Liu, Lamei; Wang, Jianan; Zhuansun, Mengyao; Xu, Tongyao; Qian, Yumeng; Dela Rosa, Ronnell (Frontiers in Public Health, 2023)
Background Chronic diseases are long-term, recurring and prolonged, requiring frequent travel to and from the hospital, community, and home settings to access different levels of care. Hospital-to-home transition is challenging travel for elderly patients with chronic diseases. Unhealthy care transition practices may be associated with an increased risk of adverse outcomes and readmission rates. The safety and quality of care transitions have gained global attention, and healthcare providers have a responsibility to help older adults make a smooth, safe, and healthy transition. Objective This study aims to provide a more comprehensive understanding of what may shape health transitions in older adults from multiple perspectives, including older chronic patients, caregivers, and healthcare providers. Methods Six databases were searched during January 2022, including Pubmed, web of science, Cochrane, Embase, CINAHL (EBSCO), and PsycINFO (Ovid). The qualitative meta-synthesis was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations. The quality of included studies was appraised using the Critical Appraisal Skills Programme (CASP) qualitative research appraisal tool. A narrative synthesis was conducted informed by Meleis's Theory of Transition. Results Seventeen studies identified individual and community-focused facilitators and inhibitors mapped to three themes, older adult resilience, relationships and connections, and uninterrupted care transfer supply chain. Conclusion This study identified potential transition facilitators and inhibitors for incoming older adults transitioning from hospital to home, and these findings may inform the development of interventions to target resilience in adapting to a new home environment, and human relations and connections for building partnerships, as well as an uninterrupted supply chain of care transfer at hospital-home delivery. Systematic review registration www.crd.york.ac.uk/prospero/, identifier: CRD42022350478.